Caregiving Burden, Acculturation, Familism, and Mexican American Elders’ Use of Home Care Services - Crist, Janice D. (Res Theory Nurs Pract, 2009)
Caregiving burden has been shown to predict use of home care services among Anglo Americans. In a previous study, only one of two dimensions of caregiving burden predicted such use among Mexican American caregivers. Because acculturation and familism may affect burden, we conducted analyses to test three hypotheses: increased acculturation decreases familism; decreased familism increases burden; and increased burden increases use of home care services. Among 140 Mexican American family caregivers, acculturation was positively correlated with familism; familism was not significantly correlated with burden; objective burden was positively correlated with use of home care services, and objective and subjective burden significantly interacted in their effect on the use of home care services. Targeted interventions may be needed to increase use of home care services and preserve the well-being of Mexican American elders and caregivers.